Properties of rice flour-gelatine-nanoclay film with catechin-lysozyme and its use for pork belly wrapping - Kanokwan Pattarasiriroj (2020)
© 2020 Elsevier Ltd The combined effect of nanoclay (NC; 5% w/w) and/or catechin-lysozyme (CL; 0.5% w/v) on the rice-flour-gelatine films’ properties was investigated. Rice-flour-gelatine film containing NC and CL exhibited the highest tensile strength (4.56 MPa), elongation at break (97.35%), and film solubility (60.79%), and the lowest film thickness (0.036 mm), compared with those of the film containing NC or CL alone. The rice-flour-gelatine film containing NC and CL, or the developed film, was chosen to apply on pork belly and qualities of wrapped pork belly throughout the storage process (4 ± 2 °C) for 7 days. This was also analysed in comparison with commercial wrap film (polyvinyl chloride; PVC). The sample wrapped with developed film exhibited lower weight loss, TBARS value, pH, and microbial growth rates, compared with the PVC-wrapped sample. It can be concluded that the developed film had a potential to be used as active food packaging.